2021
DOI: 10.1155/2021/6139732
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin C Is Involved in Macrophage M1 Polarization via p38/MAPK Pathway in Sudden Cardiac Death

Abstract: This study was aimed at identifying molecular markers associated with the pathogenesis of sudden cardiac death (SCD). It provides a proteomic analysis of human left anterior descending coronary artery from subjects diagnosed with SCD through histological examination and cases of nondisease accidental deaths through autopsy. A total of 2784 proteins were obtained from label-free quantitative proteomic analysis. This included a total of 265 differential proteins which were involved in SCD-related processes, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…2B ). As the MAPK pathway includes three main kinases, MAPK kinase kinase, MAPK kinase and MAPK, and the ERK-MAPK/P38-MAPK pathway were confirmed as important signaling cascades that plays crucial roles in angiogenesis/ macrophage polarization [ 29 , 30 ]. Then, we give a conjecture that the physiological purpose of generating SEVs accumulating miR-6750 can regulate both angiogenesis and macrophage polarization to inhibit NPC metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…2B ). As the MAPK pathway includes three main kinases, MAPK kinase kinase, MAPK kinase and MAPK, and the ERK-MAPK/P38-MAPK pathway were confirmed as important signaling cascades that plays crucial roles in angiogenesis/ macrophage polarization [ 29 , 30 ]. Then, we give a conjecture that the physiological purpose of generating SEVs accumulating miR-6750 can regulate both angiogenesis and macrophage polarization to inhibit NPC metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which the SA/BG hydrogel promoted M2 polarization remains unclear. As for the MAPK signaling pathway, it has been previously reported that the p38/MAPK pathway plays a role in IL-4-induced M2 polarization; however, some research studies also have demonstrated that p38/MAPK is involved in M1 polarization . Therefore, the role of the MAPK signaling pathway in SA/SrBG hydrogel-induced regulation of macrophage phenotype deserves to be studied in further experiments.…”
Section: Discussionmentioning
confidence: 98%
“…As for the MAPK signaling pathway, it has been previously reported that the p38/MAPK pathway plays a role in IL-4-induced M2 polarization; however, some research studies also have demonstrated that p38/MAPK is involved in M1 polarization. 53 Therefore, the role of the MAPK signaling pathway in SA/SrBG hydrogelinduced regulation of macrophage phenotype deserves to be studied in further experiments. It was also reported that the SA/BG composite hydrogel could enhance the secretion of TGFβ from the M2 macrophages, which is known to play an important role in chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, data from both animal (Hu et al 2019 ) and human (Dai et al 2021 ) studies have revealed that pathological processes resulting in heart diseases are associated with M1 macrophage polarisation, concomitantly with inhibition of M2 macrophage recruitment in the heart. For instance, Liu et al ( 2015a , b ) demonstrated M1 polarisation in a rat model of myocardial infarction along with disordered Ca 2+ waves, which stimulated the extracellular Ca 2+ receptor, CaSR, which in turn activated the NLRP3 (nucleotide-binding oligomerisation domain, leucine-rich repeats, pyrin domain-containing protein 3) inflammasome via phospholipase C (PLC)—inositol 1,4,5-triphosphate (IP3) pathway (Liu et al 2015a ).…”
Section: Contemporary View Of the Mechanisms Of Cardiac Inflammation ...mentioning
confidence: 99%